2004
DOI: 10.1093/cercor/bhg131
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Evoked Potentials, Metabolic Activity and Behavior in a Mouse Model of Somatosensory Cortex Lesion: Role of the Neural Cell Adhesion Molecule (NCAM)

Abstract: Understanding the processes that underlie functional recovery after cortical injury is a major challenge for neurobiology and clinical neurology. The aim of the present study was to establish a mouse model of functional recovery that would facilitate the investigation of the molecular and cellular events involved in cortical dynamics. We show that a focal injury of approximately 0.5 mm of diameter and 1 mm depth made in the barrel cortex of adult mice induced a transitory deficit that could be characterized us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…As detailed previously (Troncoso et al, 2000(Troncoso et al, , 2004Mégevand et al, 2008), a custom-designed electromechanical device was used for stimulating whiskers. Stimuli consisted of 300 m back-and-forth deflections with 1 ms rise time, applied to all whiskers on one side of the snout, 1 cm away from the face [30 -100 stimuli per somatosensory-evoked potential (SEP), 2-3 s interstimulus interval].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As detailed previously (Troncoso et al, 2000(Troncoso et al, , 2004Mégevand et al, 2008), a custom-designed electromechanical device was used for stimulating whiskers. Stimuli consisted of 300 m back-and-forth deflections with 1 ms rise time, applied to all whiskers on one side of the snout, 1 cm away from the face [30 -100 stimuli per somatosensory-evoked potential (SEP), 2-3 s interstimulus interval].…”
Section: Methodsmentioning
confidence: 99%
“…To verify the proper positioning of the intracortical probe, a lesion was made in the barrel or motor cortex at the end of the recordings by passing current (20 A for 8 s) through a glass microelectrode filled with Chicago Sky Blue dye and inserted at 400 m depth. Mice were then killed with pentobarbital, perfused with 4% paraformaldehyde, and the brains were extracted and processed for cytochrome oxidase histochemistry on tangential sections of the barrel cortex or for cresyl violet staining on coronal sections of the motor cortex using previously detailed protocols (Troncoso et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both PSA and p75 are known to be reexpressed in lesion contexts, such as in mechanical damage, focal ischemia, axotomy, stroke and epileptic seizures (Gage et al, 1989;Giehl et al, 2001;Kokaia et al, 1998;Rende et al, 1993;Roux et al, 1999). Remarkably, blockade or enzymatic disruption of PSA leads to an impaired repair process (Bonfanti et al, 1996; Daniloff et al, 1986) and the NCAM-knockout mice exhibit deficient recovery after cortical lesions (Troncoso et al, 2004). It has been reported that, in a mice model of amyotrophic lateral sclerosis, surviving motoneurons in transgenic animals express PSA-NCAM (Warita et al, 2001), raising the possibility that PSA re-expression protects undamaged and functional neurons from p75-mediated apoptosis.…”
Section: Developmentmentioning
confidence: 99%